Adoption of community-based strategies for sustainable vector control and prevention - Elizabeth Pellecer Rivera; Margarita Rivera Arrivillaga; José G. Juárez; Sandra M. De Urioste-Stone; Elsa Berganza; Pamela Marie Pennington (BMC, 2023)
Abstract Community engagement strategies provide tools for sustainable vector-borne disease control. A previous cluster randomized control trial engaged nine intervention communities in seven participatory activities to promote management of the domestic and peri-domestic environment to reduce risk factors for vector-borne Chagas disease. This study aims to assess the adoption of this innovative community-based strategy, which included chickens' management, indoor cleaning practices, and domestic rodent infestation control, using concepts from the Diffusion of Innovations Theory. We used questionnaires and semi-structured interviews to understand perceptions of knowledge gained, intervention adoption level, innovation attributes, and limiting or facilitating factors for adoption. The analysis process focused on five innovation attributes proposed by the Diffusion of Innovations Theory: relative advantage, compatibility, complexity, trialability, and observability. Rodent management was highly adopted by participants, as it had a relative advantage regarding the use of poison and was compatible with local practices. The higher complexity was reduced by offering several types of trapping systems and having practical workshops allowed trialability. Observability was limited because the traps were indoors, but information and traps were shared with neighbors. Chicken management was not as widely adopted due to the higher complexity of the method, and lower compatibility with local practices. Using the concepts proposed by the Diffusion of Innovations Theory helped us to identify the enablers and constraints in the implementation of the Chagas vector control strategy. Based on this experience, community engagement and intersectoral collaboration improve the acceptance and adoption of novel and integrated strategies to improve the prevention and control of neglected diseases.